Comparison of the Antidepressant-Like Effects of Estradiol and That of Selective Serotonin Reuptake Inhibitors in Middle-Aged Ovariectomized Rats - Benmansour, Saloua; Arroyo, Luis D.; Frazer, Alan (Frontiers in Aging Neuroscience, 2016)
This study investigated the effect of age and that of the post-ovariectomy (OVX) time interval on the antidepressant (AD)-like effects of estradiol (E2) and selective serotonin reuptake inhibitors (SSRIs) in middle-aged (10 month) OVX rats (10m-OVX). Acute or chronic effects of these treatments in 10m-OVX were compared with those 1) in young adult (4 month) OVX rats (4m-OVX) or with older (14 month) OVX rats (14m-OVX), at a short time: 2 weeks post-OVX (+2w) and 2) in 10m-OVX rats after a longer times: 4 or 8 months post-OVX (+4m or +8m). Using in vivo chronoamperometry in the CA3 region of the hippocampus, E2 at 20pmoles, a dose shown previously to inhibit the SERT in 4m-OVX, had no effect in 10m-OVX+2w. A higher dose of E2 (40pmoles) increased T80 value, a measure of 5-HT clearance, and also blocked the ability of fluvoxamine to increase T80. By contrast, estradiol had no effects on SERT function in 10m-OVX+4m, even at a higher dose than 40pmoles. Fluvoxamine slowed 5-HT clearance in 10m-OVX at +2w, +4m and +8m post-OVX as it did in the 4m-OVX. Using the forced swim test (FST), two weeks treatment with E2 (5μg/day), a dose shown previously to induce AD-like effects in 4m-OVX, had no effect in 10m-OVX+2w. However a higher dose (10μg/day) of E2 induced an AD-like effect as demonstrated by significantly increased swimming behavior and decreased immobility. This effect was not seen in 10m-OVX+4m. By contrast, significant AD-like effects were obtained in 14m-OVX+2w, thereby demonstrating that the lack of an antidepressant effect of E2 is due to the 4 month hormone withdrawal and not to an age effect. After two weeks treatment with the SSRI sertraline, similar AD-like effects were obtained in 10m-OVX tested at +2w, +4m or +8m post-OVX as those found in 4m-OVX. Thus, the potency of estradiol to produce effects consistent with inhibition of the SERT was not only decreased in older rats but its effects were markedly diminished the longer hormonal depletion occurred. By contrast, the ability of SSRIs to inhibit the SERT was not affected either by age or the length of hormonal depletion.